Sustainable and Green emerging trend for generation of electricity by using dyes - Singh, Gautam (International Journal of Psychosocial Rehabilitation, 2020)
Photogalvanic cells have affinity to solar energy renovation and storage. It can be efficient energy resource for future scenario, if its electrical performance is increased up to mark by using suitable combination of dyes, reductants & surfactants. In this research, the Photogalvanic cell contains Victoriaa Blue (VB) dye as photo sensitizer, Ethylene diamine tetra acetic acid (EDTA) as reluctant, Cetyl Trimethyl Ammonium Bromide (CTAB) as surfactant and Sodium hydroxide (NaOH) is used as an alkaline medium to enhance the electrical performance of batteries. The reported cell efficiency is fundamentally elevated as well. The system has conservation efficiency 1.01% and can be used in the dark for 68 Mins. Assorted parameter on which efficiency of solar energy conversion is reliant are also deliberate and account here.